Learning by exporting: The case of Mozambican manufacturing - Antonio Cruz; Carol Newman; John Rand; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
In this paper, we aim to analyse the learning by exporting hypothesis in the Mozambican context. Due to the presence of the born-global phenomenon among exporters, we address the endogeneity introduced by self-selection by combining a generalized BO approach with results from traditional matching techniques. Our results show that very few manufacturing firms export and that export participation is highly persistent. There is also evidence supporting the learning by exporting hypothesis and the results suggest a significant export premium of between 15 and 24 per cent, controlling for differences in observable characteristics between exporters and non-exporters. Finally, qualitative information on non-exporters seeking new markets suggests that 'lack of knowledge of potential markets' is the most serious constraint to international market entry. We conclude that the Mozambican Export Promotion Institute could play an important role in overcoming this information deficit for potential Mozambican exporters.
Keywords: D22; F14; O12; O55; 330; firm level analysis; export; Mozambique